Comparative Efficacy of Lorazepam and Risperidone in Hospitalized Cannabis-induced Psychotic Disorder - Arshdeep Jhalli; Ajeet Sidana; Prinka Arora (Journal of Mental Health and Human Behaviour)
Background: There is a lack of a standardized treatment protocol for cannabis-induced psychotic disorder (CIPD). Current practice involves using antipsychotics and benzodiazepines concurrently for treating CIPD. Aim: The index study aimed to assess and compare the efficacy of lorazepam against risperidone in patients with CIPD. Methods: Hospitalized patients with a diagnosis of CIPD according to the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition were randomized to receive either lorazepam or risperidone orally. Positive and Negative Syndrome Scale (PANSS), Young Mania Rating Scale (YMRS), Cannabis Withdrawal Scale, and the Marijuana Craving Questionnaire were administered at baseline and daily to assess the improvement in psychopathology, withdrawal, and craving over a period of 10 days. Monitoring was also done for any adverse effects associated with treatment. Results: A total of 40 patients with a diagnosis of CIPD were included; 20 each in lorazepam and risperidone group. Both groups were comparable with respect to baseline PANSS (P = 0.13) and YMRS (P = 0.92) scores. The baseline withdrawal score was higher in the risperidone group (P = 0.03). There was a significant reduction in PANSS and YMRS scores in both groups by day 5 and day 10 (values of <0.001). However, there was no significant difference between the two groups. The degree of improvement during the initial 5 days was significantly more (P ≤ 0.001) than that observed from day 5 to day 10 in both groups. Conclusion: There was no statistically significant difference between lorazepam and risperidone groups in terms of improvement in PANSS and YMRS scores. The use of antipsychotic did not have any additional benefit in CIPD and was rather associated with more adverse effects.